DfID's Last Stand: A Belated but Welcome Theory of Change on Mental Health and Development. (8th July 2021) - Davidson, Laura
Abstract : This article critiques the new Theory of Change (ToC) on mental health published by the UK's Department for International Development (DfID) in the last fortnight of its existence. The ToC offers development actors a framework for better support of beneficiaries with mental health conditions and psychosocial disabilities – given disappointingly scant attention by the sector to date. Yet, 70 per cent of mental disorders occur in low- and middle-income countries (LMICs), with a 22 per cent prevalence in fragile and conflict-affected states. Globally, mental ill-health is estimated to affect almost one billion people. Its intersectionality with poverty and physical health has been brought into sharp focus by the current COVID-19 pandemic which has magnified the underlying social and environmental stressors of mental health. DfID's ToC provides a conceptual framework for improving mental health globally, with an overarching vision of the full and equal exercise of all human rights by those affected by mental health conditions and psychosocial disability. The framework incorporates a rights-based approach with user-participation embedded in five critical change pathways to outcomes. The article analyses the ToC, provides an overview, highlights gaps and comments upon how DfID might have improved clarity for development actors seeking to realise its vision.